MENANGANI DISIPLIN SISWA BERMASALAH - Sarmen Refni; Rohiat Rohiat; Aliman Aliman (Manajer Pendididikan, 2017)
The purpose of this research is to describe the teamwork of teachers in dealing with student discipline problems in Senior High School Number one Tebat Karai. The method used in this research is qualitative descriptive study. The subjects were all data and information relating to the team work of teachers in handling student discipline problems. Subjects support for this reasearch are: principals, vice principals field of student, class guardian, guidance and counseling teachers, subject matter teachers, and administrative staff. Data collection techniques used are observation, documentation, and interviews. Data obtained from the research described is, in order to make a conclusion through the steps: data reduction, data presentation, and conclusion or verification. The results showed teamwork of teachers in dealing with student discipline problems have to be done well, according to the guidelines and mechanism established by the school.